FIND THE VALUE OF x :  2-2x - 3/2x + 3 = 3x +4/x+2`` ANSWER= -1`-:2`   ``

llltkl | Student

Assuming the given equation is `2-(2x-3)/(2x+3)=(3x+4)/(x+2)`

Then, `(4x+6-2x+3)/(2x+3)=(3x+4)/(x+2)`

`rArr (2x+9)/(2x+3)=(3x+4)/(x+2)`

cross multiplying we get,


`rArr 2x^2+13x+18=6x^2+17x+12`

`rArr 4x^2+4x-6=0`

Dividing both sides by 2,


This is a quadratic equation, having general solution as,

`x= (-2+-sqrt(2^2-4*2*(-3)))/(2*2)`

`=(-1+-sqrt7)/2 `

=> answer.

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question